Effectiveness Model Learning Arias (Assurance, Relevance, Interest, Assessment, and Satisfaction) Assissted Tool Figure Cards on The Materials And Reduction Additive Integrated - sabirin, desyana (Universitas Islam Negeri Antasari Banajarmasin, 2017)
This study aims to determine the effectiveness of student learning outcomes and ARIAS learning model assisted props on the material addition and subtraction of integers. This type of research is a field research with quantitative approach. The research design is pre-experimental one-group pretest-posttest. Samples were students of class VII A with total of 42 people were determined by purposive sampling. Data were collected by achievement test, interview, observation and documentation. The results showed that: (1) the average value of initial tests of students in qualifying failed at 52.54 and the average value of the final tests which are in good qualification of 80.18; and (2) ARIAS learning model props cards marked effectively used in material addition and subtraction of integers in class VII MTsN Banjar Selatan 2 with a gain value of 0.56 in the moderate category. Key Words: ARIAS learning model, integers, cards marked